A high free volume binder for the preparation of lithium ion battery electrode materials

By using high free volume polymer PTMSP as a binder in lithium-ion batteries, the problems of insufficient bondability and introduction of metal impurities in the prior art are solved, and battery performance with high energy density and long cycle life is achieved.

CN118919725BActive Publication Date: 2025-02-25CHUZHOU UNIV

Patent Information

Application Number
CN202410993515.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-02-25
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The adhesives such as PVDF in existing lithium-ion batteries have problems such as insufficient adhesion, weak mechanical strength, and the introduction of metal impurities when constructing high-energy-density batteries, which affect battery performance.

Method used

Using high free volume polymer PTMSP as the binder, a flexible self-supporting electrode without current collectors and an ultra-low binder ratio electrode was prepared by mixing different binder ratios to improve the energy density and cycle life of the battery.

Benefits of technology

Effectively reduce the internal resistance of the battery, improve the discharge capacity and cycle life, improve the mass/volume energy density of the battery, and reduce the electrochemical impedance, significantly improve the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118919725B_ABST
    Figure CN118919725B_ABST
Patent Text Reader

Abstract

The present invention relates to a high free volume binder for the preparation of lithium ion battery electrode materials. As an important component of lithium ion batteries, the binder can effectively bond active materials, conductive carbon and current collectors into a whole to ensure the stability of the electrode materials during the charge and discharge cycle. Therefore, the selection of high-performance binders is particularly important. In order to improve the electrochemical performance of lithium ion batteries and enhance their energy density, the present invention uses PTMSP as a lithium ion battery binder to obtain a flexible self-supporting electrode without current collector and an ultra-low binder ratio electrode under different binder ratios. PTMSP has a significant effect on relieving stress release during the electrode cycle, and also effectively reduces the internal resistance of the battery and improves the discharge capacity and cycle life of the battery, thereby realizing a high energy density battery. At the same time, the preparation method and process of the electrode sheet in the present invention are simple, suitable for industrial large-scale preparation, and have broad market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion batteries, and specifically relates to a method for preparing different battery pole pieces by using a high free volume polymer as a lithium ion battery binder and its application in the field of lithium ion batteries. Background Art

[0002] As an efficient energy storage device, lithium-ion batteries have become a key element in the energy field. In today's era of pursuing maximum energy efficiency, this characteristic has made lithium-ion batteries widely used in portable electronic devices such as mobile phones and electric vehicles. Lithium-ion battery electrodes are mainly composed of active materials, conductive carbon, binders, current collectors, etc. Among them, the binder plays the role of bonding the active material, conductive carbon and current collector to form a complete electrode structure. It can not only evenly disperse the active material and conductive carbon, but also help to form a good electron and ion transmission network, reduce the interface impedance of the electrode and maintain the structural integrity of the electrode. Lithium-ion batteries will expand and shrink during the charging and discharging process, which affects the battery capacity and cycle life, so the selection of efficient binders is very important.

[0003] At present, lithium-ion batteries mostly use polyvinylidene fluoride (PVDF) as a binder. However, due to its poor adhesion, weak mechanical strength, and the interaction between it and the electrode material is mainly weak van der Waals force, it has great limitations in building high-energy density batteries. In addition, the F atoms in its molecular structure are highly electronegative and easily react with positively charged substances, such as metal ions, which can easily introduce metal impurities into high-voltage electrode materials and affect battery performance.

[0004] At present, there are many patents that have made relevant reports on binders. For example, CN114976003A discloses a fluorine-free binder and a preparation method thereof, in which the molecular functional groups are modified on the molecular chain base surface of acrylic compounds or acrylonitrile compounds to form a stable macromolecular complex, which can reduce the amount of positive electrode binder used, and can further reduce the internal resistance of the battery without changing the system composition, and can reduce the amount of N-methylpyrrolidone (NMP) used, and improve the low temperature performance of the single cell. CN114597412A discloses the use of a positive electrode slurry containing a fluorine-free binder in reducing metal impurities in positive electrode sheets, by adding a fluorine-free binder including at least two copolymer monomers to the positive electrode slurry to replace the existing PVDF binder, so that the positive electrode slurry containing the fluorine-free binder will not have side reactions with the metal stirring tank during the preparation process, thereby reducing the content of metal impurities in the positive electrode slurry. Polyamide-imide (PAI) binder has also received extensive attention. CN103384009A discloses a binder. PAI is present in the form of its precursor polyamide-amic acid compound in water-based electrode slurry. The polyamide-amic acid compound is completely dissolved or mostly dissolved in water. In the electrode manufacturing process, water-based ingredient pulping is realized, and the use of high boiling point and toxic organic solvents such as NMP is avoided, which not only saves the cost of organic solvents but also avoids environmental pollution. Due to the high cohesiveness and excellent chemical and electrochemical stability of polyamide-imide, the problem of PVDF binder being unstable at high temperature, easy to decompose under high temperature conditions, and exothermic reaction with positive electrode active materials is solved, the chemical stability of the binder is improved, and the battery life and safety of use are improved. In addition, polyethyleneimine (PEI) is also a very effective tackifying resin, but because polyethyleneimine is easy to react with the carboxyl group in the water-based adhesive to form a gel, the use performance of the water-based adhesive is destroyed. CN108070057A discloses that polyethyleneimine and acrylonitrile are subjected to condensation reaction to obtain a polyethyleneimine acrylonitrile condensate. The polyethyleneimine acrylonitrile condensate can be added to a water-based adhesive (especially a carboxyl (-COOH) system) in any proportion to greatly improve its bonding performance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a high free volume binder for the preparation of lithium ion battery electrode materials, and to obtain flexible self-supporting electrodes without current collectors and ultra-low binder ratio electrodes at different binder ratios, thereby improving the mass / volume energy density and electrochemical cycle performance of the battery. The present invention applies the high free volume binder PTMSP to lithium ion batteries. Experimental results show that the binder can effectively reduce the internal resistance of the battery, improve the discharge capacity and cycle life of the battery. At the same time, the preparation method and process of the electrode sheet in the present invention are simple, suitable for large-scale industrial preparation, and have broad market application prospects.

[0006] In order to solve the technical problem of the present invention, the proposed technical solution is: a high free volume binder is used for the preparation of lithium ion battery electrode materials, comprising the following steps:

[0007] (1) Weigh the electrode material, conductive carbon and binder according to different mass ratios (60:30:10-97:2.5:0.5) and grind them in a tissue grinder for 5-10 minutes;

[0008] (2) adding a solvent to form a precursor slurry of an electrode material from the mixed material, and continuing to grind in a tissue grinder for 5-15 minutes;

[0009] (3) The obtained slurry is evenly coated on the current collector by doctor blade coating, and dried in an oven at 30° C. to 100° C. for 0.5 to 8 h;

[0010] (4) After the electrode sheet is completely cooled and dried, cut the electrode sheet according to the needs;

[0011] Wherein, the electrode material is one of lithium iron phosphate (LFP), lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium titanate (LTO), and sulfur (S) material;

[0012] The conductive carbon is one of SuperP, acetylene black and Ketjen black;

[0013] The high free volume binder is polytrimethylsilyl-1-propyne (PTMSP);

[0014] The solvent is one of toluene, tetrahydrofuran, dichloromethane and N-methylpyrrolidone;

[0015] The current collector includes one of copper foil and aluminum foil;

[0016] When the mass ratio of the binder to the electrode material, conductive carbon, and the binder mixture is 6%-12%, it can be peeled off from the current collector to obtain a flexible self-supporting electrode without a current collector; when the mass ratio of the binder to the electrode material, conductive carbon, and the binder mixture is 0.5%-2%, an ultra-low binder ratio electrode is formed.

[0017] Preferably, the conductive carbon is SuperP or Ketjen black, and the solvent is toluene or dichloromethane.

[0018] Preferably, the specific steps are as follows:

[0019] (1) The active material is LFP, the conductive carbon is SuperP, and the binder is PTMSP;

[0020] (2) weighing the active material, conductive carbon and binder in a mass ratio of 8:1:1 and grinding them in a tissue grinder for 10 min;

[0021] (3) adding toluene solvent to form a precursor slurry of electrode material from the mixed material, and continuing to grind in a tissue grinder for 10 minutes;

[0022] (4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 0.5 h;

[0023] (5) After the electrode sheet is completely dried, the obtained self-supporting electrode sheet is peeled off from the aluminum foil and sliced ​​to obtain a flexible self-supporting LFP electrode without a current collector.

[0024] Preferably, the specific steps are as follows:

[0025] (1) The active material is S, the conductive carbon is Ketjen black, and the binder is PTMSP;

[0026] (2) weighing the active material, conductive carbon, and binder in a mass ratio of 6:3:1 and grinding them in a tissue grinder for 5 min;

[0027] (3) adding dichloromethane solvent to form the above mixed material into a precursor slurry of electrode material, and continuing to grind in a tissue grinder for 15 minutes;

[0028] (4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 1 h;

[0029] (5) After the electrode sheet is completely dried, the obtained self-supporting electrode sheet is peeled off from the aluminum foil and sliced ​​to obtain a self-supporting S electrode without a current collector.

[0030] Preferably, the specific steps are as follows:

[0031] (1) The active material is LFP, the conductive carbon is SuperP, and the binder is PTMSP;

[0032] (2) The active material, conductive carbon, and binder were weighed in a mass ratio of 96:3:1 and ground in a tissue grinder for 5 min to obtain a PTMSP-LFP mixed material;

[0033] (3) Add toluene solvent to form a precursor slurry of PTMSP-LFP material, and continue grinding in a tissue grinder for 15 minutes;

[0034] (4) The obtained slurry was evenly coated on the surface of aluminum foil and dried in an oven at 100°C for 8 h. After the electrode sheet was dried, it was sliced ​​to obtain a PTMSP-LFP electrode sheet.

[0035] Preferably, the obtained PTMSP-LFP electrode sheet is used to prepare a lithium-ion battery, and a button cell of model CR2032 is used for battery assembly and testing; the battery assembly process is carried out in the order of negative electrode shell, negative electrode lithium sheet (diameter 14 mm), commercial PP diaphragm, positive electrode sheet, gasket, spring sheet, and positive electrode shell; after pressing with a battery shell pressing machine, it is taken out from the glove box and left to stand for 18 hours before the battery electrochemical performance test is carried out.

[0036] Beneficial effects:

[0037] (1) Compared with the common commercial PVDF binder, the PTMSP binder used in the present invention can form a flexible self-supporting electrode without a current collector at a mass ratio of 6%-12%, while the electrode sheet prepared by the common commercial PVDF binder at this ratio requires the support of a current collector. The advantage is that the current collector-free electrode can greatly reduce the weight and volume of the electrode sheet, and based on the mass of the positive electrode, the mass energy density of the battery can be increased by about 2-3 times.

[0038] (2) In the electrochemical cycle performance test of the battery assembled with the flexible self-supporting LFP pole piece without current collector (Example 1), at 0.2C (1C = 170 mAh g –1 ) current density, the initial discharge capacity reached 146.2 mAh g –1 After 100 cycles, the discharge capacity still remains at 144.3 mAh g –1 , with an initial capacity retention rate of up to 98.7%; based on the quality of the positive electrode, the overall energy density of the battery is increased by about 2.4 times due to the advantage of no current collector.

[0039] (3) When the high free volume binder is used at an ultra-low binder ratio (0.5wt%-2wt%), the mass ratio of the active material can be increased to 94%-97%, which is beneficial to improving the energy density of the battery; in addition, the cycle life of the battery assembled with the PTMSP binder is about 3-30 times that of the battery assembled with the PVDF binder under the same ratio conditions, and this phenomenon is more obvious at a lower binder ratio.

[0040] (4) It can be seen from the electrochemical impedance test comparison diagram of Example 3 that ( Figure 8 ), the electrochemical impedance of the battery assembled with ultra-low binder ratio electrodes was measured at different standing times. Compared with the PVDF-LFP battery, the interfacial electrochemical impedance of the PTMSP-LFP battery was about 40%-60% of the former. The reduction in resistance is beneficial to the performance of the battery to improve the charge and discharge capacity of the battery. Fig. 9It can be found from the electrochemical cycle performance comparison chart that at an ultra-low binder ratio of 1%, the capacity of the PVDF-LFP battery began to decay sharply at the 8th cycle at a current density of 0.2C, and the discharge capacity approached 0 after 40 cycles. The first cycle discharge capacity of the PTMSP-LFP battery is 148.2 mAh g –1 , after 120 cycles, the discharge capacity showed almost no significant attenuation. It can be seen that at ultra-low binder ratio, the performance of the battery assembled with PTMSP binder is far better than that of the battery assembled with commercial PVDF binder, and PTMSP binder has great application value in the field of high-performance lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a physical picture of the flexible self-supporting LFP electrode sheet prepared in Example 1 of the present invention;

[0042] Figure 2 is a scanned image of the flexible self-supporting LFP electrode sheet in Example 1 of the present invention;

[0043] Figure 3 is an electrochemical performance diagram of the flexible self-supporting LFP electrode battery in Example 1 of the present invention;

[0044] Figure 4 This is a physical picture of the flexible self-supporting S electrode sheet prepared in Example 2 of the present invention;

[0045] Figure 5 This is a scanned image of the flexible self-supporting S electrode sheet in Example 1 of the present invention;

[0046] Figure 6 is an electrochemical performance diagram of the flexible self-supporting S-electrode battery in Example 2 of the present invention;

[0047] Figure 7 This is a scan of the LFP electrode sheet prepared in Example 3 of the present invention at a binder ratio of 1%;

[0048] Figure 8 1 is a comparison diagram of electrochemical impedance of PVDF and PTMSP binder batteries in Example 3 of the present invention (different standing times);

[0049] Fig. 9 is a comparison chart of the cycle performance of PVDF and PTMSP binder batteries in Example 3 of the present invention; DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0051] The specific implementation of the present invention is further described below in conjunction with the technical solution.

[0052] Example 1

[0053] 1) The active material is LFP, the conductive carbon is SuperP, and the binder is PTMSP;

[0054] 2) weighing the active material, conductive carbon and binder in a mass ratio of 8:1:1 and grinding them in a tissue grinder for 10 minutes;

[0055] 3) adding toluene solvent to form the precursor slurry of the electrode material from the above mixed materials, and continuing to grind in a tissue grinder for 10 minutes;

[0056] 4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 0.5 h;

[0057] 5) After the electrode sheet is completely dried, the obtained self-supporting electrode sheet is peeled off from the aluminum foil and sliced ​​to obtain a self-supporting LFP electrode without a current collector;

[0058] 6) In this experimental exploration, CR2032 button batteries were used for battery assembly and testing;

[0059] 7) The battery assembly process is carried out in the order of negative electrode shell, negative electrode lithium sheet (diameter 14 mm), commercial PP separator, positive electrode sheet, gasket, spring, and positive electrode shell;

[0060] 8) After the battery shell pressing machine is used to press, the battery is taken out from the glove box and allowed to stand for 18 hours before the battery electrochemical performance test is performed.

[0061] Example 2

[0062] 1) The active material used is S, the conductive carbon is Ketjen black, and the binder is PTMSP;

[0063] 2) weighing the active material, conductive carbon and binder in a mass ratio of 6:3:1 and grinding them in a tissue grinder for 5 minutes;

[0064] 3) adding dichloromethane solvent to form the above mixed material into a precursor slurry of electrode material, and continuing to grind in a tissue grinder for 15 minutes;

[0065] 4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 1 h;

[0066] 5) After the electrode sheet is completely dried, the obtained self-supporting electrode sheet is peeled off from the aluminum foil and sliced ​​to obtain a self-supporting S electrode without a current collector;

[0067] 6) In this experimental exploration, CR2032 button batteries were used for battery assembly and testing;

[0068] 7) The battery assembly process is carried out in the order of negative electrode shell, negative electrode lithium sheet (diameter 14 mm), commercial PP separator, positive electrode sheet, gasket, spring, and positive electrode shell;

[0069] 8) After the battery shell pressing machine is used to press, the battery is taken out from the glove box and allowed to stand for 18 hours before the battery electrochemical performance test is performed.

[0070] Example 3

[0071] 1) The active material is LFP, the conductive carbon is SuperP, and the binders are PTMSP and PVDF respectively;

[0072] 2) The active material, conductive carbon, and binder were weighed in a mass ratio of 96:3:1 and ground in a tissue grinder for 5 min to obtain PTMSP-LFP and PVDF-LFP mixed materials, respectively;

[0073] 3) Add toluene solvent to form the PTMSP-LFP material into precursor slurry A, and continue grinding in the tissue grinder for 15 minutes;

[0074] 4) adding N-methylpyrrolidone solvent to form the PVDF-LFP material into precursor slurry B, and continuing to grind in the tissue grinder for 15 minutes;

[0075] 5) The obtained slurries A and B are respectively evenly coated on the surface of aluminum foil, dried in an oven at 100°C for 8 hours, and sliced ​​after the electrode pieces are dried to obtain PTMSP-LFP electrodes and PVDF-LFP electrode sheets, respectively;

[0076] 6) In this experimental exploration, CR2032 button batteries were used for battery assembly and testing;

[0077] 7) The battery assembly process is carried out in the order of negative electrode shell, negative electrode lithium sheet (diameter 14 mm), commercial PP separator, positive electrode sheet, gasket, spring, and positive electrode shell;

[0078] 8) After the battery shell pressing machine is used to press, the battery is taken out from the glove box and allowed to stand for 18 hours before the battery electrochemical performance test is performed.

[0079] In Examples 1 and 2, 10% PTMSP binder was used to prepare current collector-free self-supporting electrode sheets for lithium iron phosphate batteries and lithium sulfur batteries. The electrode sheets had certain flexibility and did not break after being bent 180 degrees under tweezers compression ( Figure 1 , 4 ).

[0080] We then observed the microscopic morphology of the electrode sheets in Examples 1 and 2 using a scanning electron microscope. We can see that the surface of the self-supporting electrode sheet is relatively uniform and flat, without obvious cracks. The surface of the electrode material and the conductive carbon particles are wrapped by a layer of polymer ( Figure 2 , 5 ), which is conducive to maintaining the stability of the electrode sheet during the cycle and achieving a long cycle life. Therefore, the battery assembled with this kind of flexible self-supporting electrode sheet without current collector has a lighter weight and thinner thickness, which can obtain a more competitive high quality / volume energy density battery.

[0081] In the electrochemical cycle performance test of the battery assembled with the flexible self-supporting LFP pole piece without current collector (Example 1), at 0.2C (1C = 170 mAh g –1 ) current density, the initial discharge capacity reached 146.2 mAh g –1 After 100 cycles, the discharge capacity still remains at 144.3 mAh g –1 , with an initial capacity retention rate of up to 98.7%; based on the quality of the positive electrode, the overall energy density of the battery is increased by about 2.4 times due to the advantage of no current collector.

[0082] In the performance test of the lithium-sulfur battery in Example 2, the maximum discharge capacity at a current density of 0.2C is 977.6 mAh g –1 After 250 cycles, it still has 662.6 mAh g –1 The discharge capacity is 2.38W and the Coulombic efficiency is over 98% during the entire cycle.

[0083] In Example 3, Figure 7 This is the SEM image of the ultra-low binder ratio electrode under a scanning electron microscope. Compared with the PVDF-LFP electrode, it can be seen that the PTMSP-LFP electrode has more filamentous bonding between the active material and the conductive carbon. This highly adhesive structure can ensure the stability of the electrode material during the cycle, and the electrode particles are not easy to fall off during the charge and discharge process.

[0084] It can be seen from the electrochemical impedance test diagram of Example 3 that ( Figure 8 ), the electrochemical impedance of the battery assembled with electrodes of ultra-low binder ratio was measured at different standing times. Compared with the PVDF-LFP battery, the interfacial electrochemical impedance of the PTMSP-LFP battery was smaller, about 40%-60% of the former. The reduction of resistance is beneficial to the performance of the battery and improves the charge and discharge capacity of the battery.

[0085] exist Fig. 9 It can be found from the electrochemical cycle performance comparison chart that at an ultra-low binder ratio of 1%, the capacity of the PVDF-LFP battery began to decay sharply at the 8th cycle at a current density of 0.2C, and the discharge capacity approached 0 after 40 cycles, and the coulomb efficiency was unstable during the cycle. The first cycle discharge capacity of the PTMSP-LFP battery was 148.2 mAh g –1 After 120 cycles, the discharge capacity retention rate is as high as 98.9%, and there is almost no obvious capacity decay. It can be seen that at an ultra-low binder ratio, the performance of the battery assembled with PTMSP binder is far better than that of the battery assembled with commercial PVDF binder. PTMSP binder has great application value in the field of high-performance lithium-ion batteries.

[0086] In summary, the introduction of PTMSP binder has a certain promoting effect on maintaining the stability of the electrode structure during the cycle and reducing the electrochemical interface impedance of the battery, effectively improving the discharge capacity and cycle life of the battery, and realizing a high energy density lithium ion battery. At the same time, the preparation method and process of the electrode sheet in the present invention are simple, suitable for industrial large-scale preparation, and have broad market application prospects.

[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high free volume binder for use in the preparation of lithium ion battery electrode materials, characterized in that: The steps include: (1) Weigh the electrode material, conductive carbon and binder according to different mass ratios and grind them in a tissue grinder for 5-10 min; (2) adding a solvent to form a precursor slurry of the electrode material from the mixed material, and continuing to grind in a tissue grinder for 5-15 minutes; (3) The obtained slurry is evenly coated on the current collector by blade coating, and dried in an oven at 30°C-100°C for 0.5-8 h; (4) After the electrode is completely cooled and dried, it is sliced ​​according to needs; Wherein, the electrode material is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, lithium titanate, and sulfur material; The conductive carbon is one of SuperP, acetylene black and Ketjen black; The high free volume binder is polytrimethylsilyl-1-propyne PTMSP; The solvent is one of toluene, tetrahydrofuran, dichloromethane and N-methylpyrrolidone; The current collector includes one of copper foil and aluminum foil; By setting the mass ratio of the binder to the electrode material, the conductive carbon, and the binder mixture to 6%-12%, a flexible self-supporting electrode without a current collector is obtained by peeling it off from the current collector.

2. The high free volume binder according to claim 1 is used for the preparation of lithium ion battery electrode materials, characterized in that: The conductive carbon is SuperP or Ketjen black, and the solvent is toluene or dichloromethane.

3. The high free volume binder according to claim 1 is used for the preparation of lithium ion battery electrode materials, characterized in that: The specific steps are as follows: (1) The active material is LFP, the conductive carbon is SuperP, and the binder is PTMSP; (2) The active material, conductive carbon and binder were weighed in a mass ratio of 8:1:1 and ground in a tissue grinder for 10 min; (3) Add toluene solvent to form a precursor slurry of electrode material from the mixed material, and continue grinding in a tissue grinder for 10 min; (4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 0.5 h; (5) After the electrode is completely dried, the self-supporting electrode is peeled off the aluminum foil and sliced ​​to obtain a flexible self-supporting LFP electrode without a current collector.

4. The high free volume binder according to claim 1 is used for the preparation of lithium ion battery electrode materials, characterized in that: The specific steps are as follows: (1) The active material used is S, the conductive carbon is Ketjen black, and the binder is PTMSP; (2) The active material, conductive carbon, and binder were weighed in a mass ratio of 6:3:1 and ground in a tissue grinder for 5 min; (3) adding dichloromethane solvent to form the above mixed material into a precursor slurry of electrode material, and continuing to grind in a tissue grinder for 15 min; (4) The obtained slurry was evenly coated on aluminum foil and dried in an oven at 30°C for 1 h; (5) After the electrode is completely dried, the obtained self-supporting electrode is peeled off from the aluminum foil and sliced ​​to obtain a flexible self-supporting S electrode without a current collector.

5. The high free volume binder according to claim 3 is used for the preparation of lithium ion battery electrode materials, characterized in that: The obtained PTMSP-LFP electrode sheet was used to prepare lithium-ion batteries, and button batteries with model CR2032 were used for battery assembly and testing; the battery assembly process was carried out in the order of negative electrode shell, negative electrode lithium sheet with a diameter of 14 mm, commercial PP separator, positive electrode sheet, gasket, spring, and positive electrode shell; after being pressed with a battery shell press, it was taken out from the glove box and left to stand for 18 hours before the battery electrochemical performance test.

Citation Information

Patent Citations

  • Electrode active material composition, electrode and lithium ion secondary battery

    CN103384009A

  • Polyethylenimine acrylonitrile condensation compound and modified aqueous binder

    CN108070057A

  • Application of positive electrode slurry containing fluoride-free binder in reduction of metal impurities in positive electrode plate

    CN114597412A

  • Fluorine-free binder as well as preparation method and application thereof

    CN114976003A

  • Negative pole binder, negative pole piece and lithium ion secondary battery

    CN109428080A

Cited By

  • Metal-free current collector integrated self-supporting electrode and preparation method and application thereof

    CN122348183A